The Drosophila Fab-7 boundary modulates Abd-B gene activity by guiding an inversion of collinear chromatin organization and alternate promoter use. - Moniot-Perron, L.; Moindrot, B.; Manceau, L.; Edouard, J.; Jaszczyszyn, Y.; Gilardi-Hebenstreit, P.; Hernandez, C.; Bloyer, S.; Noordermeer, D. (Cell reports, 2023)
Hox genes encode transcription factors that specify segmental identities along the anteroposterior body axis. These genes are organized in clusters, where their order corresponds to their activity along the body axis, a feature known as collinearity. In Drosophila, the BX-C cluster contains the three most posterior Hox genes, where their collinear activation incorporates progressive changes in histone modifications, chromatin architecture, and use of boundary elements and cis-regulatory regions. To dissect functional hierarchies, we compare chromatin organization in cell lines and larvae, with a focus on the Abd-B gene. Our work establishes the importance of the Fab-7 boundary for insulation between 3D domains carrying different histone modifications. Interestingly, we detect a non-canonical inversion of collinear chromatin dynamics at Abd-B, with the domain of active histone modifications progressively decreasing in size. This dynamic chromatin organization differentially activates the alternative promoters of the Abd-B gene, thereby expanding the possibilities for fine-tuning of transcriptional output.